Pengembangan interior Gereja Katolik Santo Petrus Sambiroto berbasis liturgi-partisipatif: Liturgical participatory interior development of St. Peter’s Church - Rihadiani, Rosalia; Setiawan, Fl. B.; Saraswati, Ratih D.; Kriswari, Maria D.; Palilih, Lindu; Rejeki, VG. S. (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT The interior of Saint Peter’s Catholic Church in Sambiroto, Semarang, has not created a fully supportive atmosphere conducive to solemn liturgical worship. Based on observations and interviews with church administrators, several issues were identified, including the overlap between the central cross and the projection screen, as well as lighting and decorative elements that failed to enhance the spiritual ambience. This community engagement project aimed to redesign the church interior using a liturgy-based. The method employed a design-based inquiry that combined field observation, participatory discussions, a review of the literature, and a spatial needs analysis. The output is a comprehensive interior design document that emphasizes the sacred zone through the repositioning of the altar and tabernacle, thematic stained glass, hierarchical lighting, and carefully integrated visual communication technologies. The design was validated in collaboration with the Parish Council and Pastor, and is intended for submission to the Archdiocese of Semarang. This project demonstrates that a participatory approach grounded in theological principles can yield meaningful and functional church interiors that enhance the worship experience of the congregation. Keywords: Catholic church; interior desig;, sacred atmosphere; liturgy;, community service ABSTRAK Interior Gereja Katolik Santo Petrus Sambiroto di Semarang belum sepenuhnya menciptakan suasana sakral yang mendukung proses liturgi. Berdasarkan observasi dan wawancara dengan pengelola gereja, ditemukan sejumlah permasalahan seperti tumpang tindih antara salib utama dan layar proyektor, serta penataan pencahayaan dan elemen dekoratif yang tidak mendukung atmosfer ibadah. Kegiatan pengabdian ini bertujuan merancang ulang interior gereja dengan pendekatan berbasis liturgi. Metode yang digunakan adalah design-based inquiry dengan kombinasi observasi, diskusi partisipatif, studi literatur dan analisis kebutuhan ruang. Hasil kegiatan berupa dokumen desain interior yang menegaskan zona sakral melalui penataan ulang altar, tabernakel, kaca patri tematik, pencahayaan hierarkis, serta elemen teknologi komunikasi visual yang tertata harmonis. Validasi rancangan dilakukan bersama Dewan Pastoral dan Pastor Paroki, serta diarahkan sebagai bahan pengajuan resmi ke Keuskupan Agung Semarang. Hasil ini menunjukkan bahwa pendekatan partisipatif yang berlandaskan prinsip teologis mampu menghadirkan desain interior gereja yang bermakna, fungsional, dan memperkuat pengalaman iman umat. Kata kunci: Gereja Katolik; Desain interior; suasana sakral; liturgi; pengabdian Masyarakat